WNT signaling in development and disease - Yamaguchi, Terry P.; Willert, Karl (Current topics in developmental biology ;, 2023)
Wnt Signaling in Development and Disease, Volume 153 in the Current Topics in Developmental Biology series, highlights new advances in the field, with this new volume presenting interesting chapter on topics such as The cell biology of Wnt gradient formation, Approaches to visualize and trace Wnt signaling in vitro and in vivo, WNT signaling and the regulation of pluripotency, Wnt/Frizzled signaling in stem cells in development and cancer, Wnt signaling in hydra development and regeneration, Wnt signaling in whole body regeneration, Role of planar cell polarity and Wnt signaling in left-right asymmetry, Wnt signaling in axial progenitors, and more. Other chapters cover Wnt signaling in Xenopus neural development, Wnt signaling in hematopoietic stem cell development, Wnt signaling and the maintenance and regeneration of the gut epithelium, Wnt signaling in the skeleton as a basis for Wnt-based regenerative medicine, and Non-canonical Wnt5a-Ror signaling: Insights from human congenital disorders and cancer. Provides the authority and expertise of leading contributors from an international board of authors Presents the latest release in the Current Topics in Developmental Biology series Updated release includes the latest information on Wnt Signaling in Development and Disease.